Analisis pertanggungjawaban keuangan Pondok Pesantren di Kecamatan Praya Barat - Baiq, Krisnina Maharani Putri; Mujahidi, Khairul; Aptasari, Fety Widianti; Hastuti, Ely Windarti (Journal of Accounting and Digital Finance, 2024)
This research is intended to find out how the financial reporting of boarding schools in West Praya Sub-district and the reasons why each boarding school has not yet conducted financial reporting in accordance with the Islamic Boarding School Accounting Guidelines. The research method used is qualitative research with a descriptive approach. The process of collecting data is done by interviews and documentation. This research was conducted in thirteen (13) boarding school foundations in West Praya Sub-district. The results of this study indicate that the financial reports made by each boarding school foundation in West Praya Sub-district are not in accordance with the Boarding School Accounting Guidelines, and there are several forms of financial responsibility. The reasons why boarding schools in West Praya Sub-district have not made financial reports in accordance with the Islamic Boarding School Accounting Guidelines are boarding schools do not know about the Boarding School Accounting Guidelines, there are no adequate human resources (HR), there are no permanent donors, the funds come from private funds, and the last reason is that there is no demand from donors for the boarding school foundation to make financial reports in accordance with the Islamic Boarding School Accounting Guidelines.